2012
DOI: 10.1080/17470218.2012.694896
|View full text |Cite
|
Sign up to set email alerts
|

The role of numerosity in processing nonsymbolic proportions

Abstract: The difficulty in processing fractions seems to be related to the interference between the whole-number value of the numerator and the denominator and the real value of the fraction. Here we assess whether the reported problems with symbolic fractions extend to the nonsymbolic domain, by presenting fractions as arrays of black and white dots representing the two operands. Participants were asked to compare a target array with a reference array in two separate tasks using the same stimuli: a numerosity task com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 26 publications
5
34
5
Order By: Relevance
“…As expected, we found that the bias changes with the probability of observing a large numerator in the larger fraction. Perhaps more interesting, we replicated previous findings that the bias persists in the balanced 50/50 condition (Alonso-Diaz et al, 2018;Fabbri, Caviola, Tang, Zorzi, & Butterworth, 2012). It is a common but strange result for the adaptation theory: with balanced probabilities, the bias should disappear, i.e., picking based on the numerator will lead to chance-behavior.…”
Section: Prior Beliefs As a (Partial) Explanation For Numerator Stratsupporting
confidence: 85%
“…As expected, we found that the bias changes with the probability of observing a large numerator in the larger fraction. Perhaps more interesting, we replicated previous findings that the bias persists in the balanced 50/50 condition (Alonso-Diaz et al, 2018;Fabbri, Caviola, Tang, Zorzi, & Butterworth, 2012). It is a common but strange result for the adaptation theory: with balanced probabilities, the bias should disappear, i.e., picking based on the numerator will lead to chance-behavior.…”
Section: Prior Beliefs As a (Partial) Explanation For Numerator Stratsupporting
confidence: 85%
“…Participants performed quickly and accurately on a perceptually based task comparing nonsymbolic ratio magnitudes, adding to recent work demonstrating human perceptual sensitivity to nonsymbolic ratio magnitudes in various formats (e.g., Bonn & Cantlon, 2017;Duffy, Huttenlocher, & Levine, 2005;Jacob et al, 2012;Lewis, Matthews, & Hubbard, 2015;Mock et al, 2018; see also Spence, 1990;Stevens & Galanter, 1957;Hollands & Dyre, 2000). This stands alongside recent work showing that this ratio perception is in some respects automatic (Fabbri, Caviola, Tang, Zorzi, & Butterworth, 2012;Yang, Hu, Wu, & Yang, 2015) and that humans seem to represent nonsymbolic ratio magnitudes as specific values instead of as nondescript generalized magnitudes less than one (Matthews & Chesney, 2015;; but see Kallai & Tzelgov, 2009). Moreover, the work also stands alongside research showing that nonsymbolic ratio perception extends to nonhuman primates (e.g., Drucker et al, 2016;Vallentin & Nieder, 2008) and other animals (e.g., McComb, Packer, & Pusey, 1994;Rugani, McCrink, de Hevia, Vallortigara, & Regolin, 2016).…”
Section: Replicating Ratio Perceptionmentioning
confidence: 61%
“…The interference between absolute number and relative proportion has been at the center of a substantial amount of work with symbolic (e.g., Alibali & Sidney, 2015;Durkin & Rittle-Johnson, 2015;Ni & Zhou, 2005) and non-symbolic representations (e.g., Boyer et al, 2008;Boyer & Levine, 2015;Fabbri, Caviola, Tang, Zorzi, & Butterworth, 2012;Hurst & Cordes, 2018a;Jeong, et al, 2007). The interference between absolute number and relative proportion has been at the center of a substantial amount of work with symbolic (e.g., Alibali & Sidney, 2015;Durkin & Rittle-Johnson, 2015;Ni & Zhou, 2005) and non-symbolic representations (e.g., Boyer et al, 2008;Boyer & Levine, 2015;Fabbri, Caviola, Tang, Zorzi, & Butterworth, 2012;Hurst & Cordes, 2018a;Jeong, et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…When proportion is presented discretely (i.e., with distinct, divided units that can be explicitly counted, like a bag of candy or a rectangle divided into quarters), this countable numerical information may be particularly salient and can interfere with our ability to focus on the relation between the two components. The interference between absolute number and relative proportion has been at the center of a substantial amount of work with symbolic (e.g., Alibali & Sidney, 2015;Durkin & Rittle-Johnson, 2015;Ni & Zhou, 2005) and non-symbolic representations (e.g., Boyer et al, 2008;Boyer & Levine, 2015;Fabbri, Caviola, Tang, Zorzi, & Butterworth, 2012;Hurst & Cordes, 2018a;Jeong, et al, 2007). In particular, the availability of countable, discrete quantities leads to systematic and predictable errors in the way children respond in proportion tasks.…”
Section: Introductionmentioning
confidence: 99%